2016
DOI: 10.1039/c6ra16432c
|View full text |Cite
|
Sign up to set email alerts
|

Stearylated cycloarginine nanosystems for intracellular delivery – simulations, formulation and proof of concept

Abstract: Novel cationic agent liposomes performed better in silico translating in higher cellular uptake with reduced toxicity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 54 publications
0
6
0
Order By: Relevance
“…For a recent review of lipid diversity, please read refs . In spite of this variety, artificial lipids are actively developed for pharmaceutical applications or as research tools. For reviews, see refs .…”
Section: Biomembranes As the Target Of Simulations: Native Membranes ...mentioning
confidence: 99%
“…For a recent review of lipid diversity, please read refs . In spite of this variety, artificial lipids are actively developed for pharmaceutical applications or as research tools. For reviews, see refs .…”
Section: Biomembranes As the Target Of Simulations: Native Membranes ...mentioning
confidence: 99%
“…An organ with the highest cholesterol content is the brain, particularly the myelin sheets insulating the axons . There are also various cholesterol-rich biomaterial applications mimicking nature, such as liposomes used in drug delivery, where high cholesterol content prevents leakage of encapsulated drugs. This is a common strategy in currently approved therapies based on liposomes as drug carriers. , …”
Section: Introductionmentioning
confidence: 99%
“…Percent hemolysis values below 10% were considered to be nonhemolytic. 62 It was observed that formulated cationic RL5 caused 1.88% hemolysis, which is under the permissible limit (less than 10% lysis). Hemolysis assay suggests that the concentration of SA used in the formulation of RL5 is blood biocompatible and can be used for in vivo administration.…”
Section: Resultsmentioning
confidence: 96%
“…In the present investigation, RL5 formulation (equivalent to 20 mg/mL RS) and free RS (20 mg/mL) were evaluated for hemolysis as compared to positive control (1% w/v Triton in PBS) and negative control (0.1% v/v DMSO in PBS), as depicted in Figure S2. Percent hemolysis values below 10% were considered to be nonhemolytic . It was observed that formulated cationic RL5 caused 1.88% hemolysis, which is under the permissible limit (less than 10% lysis).…”
Section: Resultsmentioning
confidence: 99%